Application of the Make A Match Learning Model in Material on the Diversity of Traditional Houses in Indonesia Class IV SD Negeri 13 Simeulue Timur - Aszahra, Nesa; Husin, M.; Fitri, Aida (Elementary Education Research, 2024)
This study aims: 1) to find out student activities through the application of the learning model make a match on the material on the diversity of traditional houses in Indonesia class IV SD Negeri 13 Simeulue Timur 2) to find out student learning outcomes through the application of the make a match learning model on material on traditional diversity in Indonesia class IV SD Negeri 13 Timur.The approach in this research is qualitative and The type is descriptive.The research subjects were 21 grade IV students of SD Negeri 13 Simeulue Timur. In collecting this data using observation sheets of student activity instruments, as well as tests of student learning outcomes. Data were analyzed using the percentage formula. Based on the results of research data analysis, it can be concluded that student activity when applying the make a match learning model in learning at the first meeting was still with good criteria, namely the average value of 3.05 and at the second meeting increased, namely 3.70 with very good criteria. In the first meeting the results of learning completeness were incomplete with a percentage value of 66.66% and at the second meeting it increased to 90.47%. So in this study it can be concluded that the application of the make a match model in class IV SD Negeri 13 Simeulue Timur can increase student activity and student learning outcomes for the better.